Improved flame retardant of intumescent flame retardant flame-retarded high density polyethylene with fullerene decorated by iron compound - Y. Q. Pan (eXPRESS Polymer Letters, 2019)
Fullerene decorated by iron compound (C60-Fe) was fabricated via solution reaction and characterized by X-ray photoelectron spectra and wide-angle X-ray diffraction. By a partial replacement of intumescent flame retardant (IFR) in flame retarded polyethylene (PE) by C60-Fe, the flame retardant properties of PE/IFR composites were increased dramatically. When 2 wt% IFR was substituted by C60-Fe, a compact and continuous char barrier was formed, resulting in the reduction of the peak of heat release rate (PHRR) and the total heat released (THR). Also, the ignition time (tign) prolonged form 67 to 114 s and the time to PHRR (tPHRR) prolonged form 208 to 455 s. The improvement on flame retardancy of PE/IFR/C60-Fe composites was due to the synergistic influence between the catalytic charring ability of Fe and the free radical trapping effect of C60.